Assembling sovereignty: Canadian claims to the Athabasca district prior to Treaty No. 8 - Irwin, Robert (My University, 2020)
Recent Canadian legal scholarship has emphasised the centrality of treaties between the colonial state and First Nations in the assertion of Canadian sovereignty over Indigenous lands. Historical interpretations, meanwhile, would suggest that sovereignty, rather than asserted, is assembled over time. Historically, sovereignty is understood to be contingent and layered; it is assembled through a series of ‘detours, improvisations and tinkering.’ This paper looks at the historical circumstances of Canadian sovereignty in the Athabasca district prior to the making of Treaty No. 8 with the First Nations. British sovereignty claims to Rupert's Land and the Northwestern Territories (including the area that came to be known as the Athabasca district), were assembled through the practices and activities of the Hudson's Bay Company. These claims were transferred to Canada in 1869 and Canada hesitantly and quietly took measures to further assemble and express its sovereignty in these lands. Canada surveyed and inventoried the Athabasca district's resources, commenced exploratory work on petroleum resources, provided relief from famine, financially supported schools for Indigenous children, and established and enforced a system of law. By the time Treaty No. 8 was negotiated in 1899, Canada had thus taken a series of steps to assemble and express its sovereignty in the district. Rather than establishing, asserting or legitimating Canadian sovereignty, Treaty No. 8 may be better understood as another measure in the process of assembling it.
Keywords: Canada; sovereignty; Indigenous peoples; famine; Treaty 8